Best Practice Of Sustainable Halal Tourism In Rubiah Island, Sabang, Indonesia - Ajidin, Zilal Afwa; Suhara, Ade Idra; Kariman, Zul; Hasibuan, Rahmat Putra Ahmad (LPPM ISNJ Bengkalis, 2024)
This study aims to investigate implementing sustainable halal tourism practices on Rubiah Island, Sabang, Indonesia, emphasizing the integration of local wisdom rooted in Acehnese culture and Islamic Sharia principles. The study examines how these elements contribute to a unique form of tourism that respects religious and cultural diversity. Using a qualitative descriptive approach, data were collected through literature review, stakeholder interviews, and field observations. Data analysis involved thematic analysis to identify recurring themes and insights regarding the influence of Acehnese local wisdom and Islamic Sharia principles on tourism practices on the island. Key sustainable tourism practices include halal-certified activities such as environmentally responsible snorkeling, promoting hospitality, and dolphin-friendly tourism that minimizes disturbances to marine habitats. Notably, Rubiah Island adheres to a policy of no permanent structures, maintains curated tour packages, highlights its historical significance, and is near protected forest areas. These efforts underscore Rubiah Island's commitment to sustainable tourism principles, aiming to preserve its natural beauty and cultural heritage while providing a halal-friendly experience for visitors. This research contributes to understanding how sustainable practices can be harmoniously integrated with Islamic values and local customs to enhance tourism development in Aceh.